480 Preliminary evaluation of a novel coronavirus vaccine (CORVax) using electroporation of plasmid DNA encoding a stabilized prefusion SARS-CoV-2 spike protein alone or with transfection of plasmid IL-12. (9th November 2020) - Jensen, Shawn; Twitty, Christopher; Paustian, Christopher; Laws, Madelein; McDonnell, Glenna; Wegmann, Keith; Moudgil, Tarsem; Afentoulis, Michael; Han, Mia; Foerter, Kellie Malloy; Canton, David; Lee, Jack; et al.
Abstract : Background: SARS-CoV-2 (CoV2) has precipitated a global pandemic and the effectiveness of standard vaccine strategies to induce potent and persistent immunity to CoV2 is in question, particularly for the elderly. This problem is not dissimilar to what we have struggled with in our quest to induce immunity to cancer antigens, where vaccine-induced anti-cancer immune responses can be weak. Here, we describe a novel vaccine approach which leverages electroporation (EP) of a plasmid encoding a prefusion stabilized CoV2 spike protein (CORVax). As IL-12 has been shown to augment the efficacy of immunotherapy in aged mice, 1 we have initiated studies to evaluate if plasmid IL-12 (TAVO™) can similarly augment anti-CoV2 immune responses in young mice and have planned studies in aged animals. Methods: A prefusion stabilized CoV2 spike plasmid expression vector was constructed, a master cell bank generated and clinical-grade plasmid manufactured. C57BL/6 and BALB/c were vaccinated via intramuscular (IM) and/or intradermal (ID) injection followed immediately by EP of plasmids encoding the CoV2 spike protein with or without plasmid-encoded murine IL-12 on days 1 and 14 or 21. Mice were followed for >120 days to assess safety. Splenocytes and serum were harvested at different time points to interrogate virus-specific cellular responses as well anti-spike IgG1/IgG2 antibody titers. A surrogate viral neutralization test (sVNT) assessed serum blockade of soluble hACE2R binding to immobilized CoV2 spike. Results: Preliminary data shows that EP of CORVax alone or combined with IL-12 was safe. EP of CORVax was able to elicit anti-Spike IgG antibodies (IC50 = 1/2112), as well as IgG antibodies targeting the receptor binding domain of the Spike protein (IC50 = 1/965) approximately 40 days after the booster vaccination. In 2 of 2 experiments, CORVax combined with IL-12 significantly (P<0.0001) increased the sVNT titers at 2 months, but this benefit was lost by 3 months. Conclusions: Early preclinical data shows that EP of CORVax can induce IgG responses to CoV2 Spike and the receptor binding domain (RBD) as well as apparent viral neutralizing activity. The addition of IL-12, at least transiently, increased sVNT titer. We plan to investigate alternate vaccine boosting strategies while extending these studies into aged animals and initiate a clinical trial in the near future. References: Ruby CE, Weinberg AD. OX40-Enhanced tumor rejection and effector T cell differentiation decreases with age. J Immunol 2009;182 :1481–9. https://doi.org/10.4049/jimmunol.182.3.1481.